Excision of Prostatic Utricle: When? How? - Gökhan Karakurt; Hakan Keskin; Hasan Serkan Doğan; Serdar Tekgül (Journal of Urological Surgery)
The prostatic utricle is a rare anomaly in the urogenital system and is generally thought to develop from remnants of the Müllerian duct. Prostatic utricle is usually accompanied by hypospadias, renal agenesis, and cryptorchidism, and it is mostly asymptomatic. Symptoms such as recurrent urinary tract infection, epididymo-orchitis, abdominal pain, voiding disorders, and stones are observed. Surgery in symptomatic patients is recommended. Prostatic utricle cyst was detected as a result of abdominal imaging in two of our patients who had a history of hypospadias repairs, and who presented with complaints of recurrent epididymo-orchitis and abdominal pain. We report two cases of laparoscopic utricle cyst excision.